Congenital Cutis Laxa: A Case Report and Literature Review - Kun, Yang; Mengdong, Shi; Cong, Fu; Ran, Huo (Frontiers in Surgery, 2022)
Cutis Laxa is a rare connective tissue disease featuring inelastic and saggy skin. It is thought that plastic surgery might be the most effective treatment, while the previous literatures on the surgical treatment for Cutis Laxa complained of the recurrence. We report a patient of Congenital Cutis Laxa who has received systematic and sequential treatment based on plastic surgery. The patient is content with the effect of treatment and there are no signs of recurrence after 5months. By referring to relevant literatures, we evaluate the clinical manifestations and diagnosis of the disease. A multi-step, systematic and sequential treatment is recommended for the treatment of Congenital Cutis Laxa.